Práticas lúdicas no ensino da matemática para alunos com transtorno do espectro autista do ensino fundamental - FERREIRA, André Luiz Noronha (2022)
This research seeks to analyze how playful practices can contribute to the teaching of Mathematics to students with Autism Spectrum Disorder in Elementary School. More specifically, it seeks to identify the pedagogical practices of Mathematics teachers for students with Autism Spectrum Disorder, to understand the teachers' conceptions about teaching for these students, as well as to theoretically discuss the implications of using this didactic tool. The study has a qualitative approach, in which a field and bibliographic research was developed. The field research was carried out in two schools, one public and the other private, in which questionnaires were applied to four Mathematics teachers from Elementary School. The results and analyzes show that many mathematics professionals, mostly, because they do not have specific training to teach autistic students, have numerous difficulties to teach their different contents and that they need to work through different strategies. In this context, playful practices are significant activities that provide these students with a greater participation in the teaching and learning process.